A molecular framework for the identification of planthopper vectors (Hemiptera: Delphacidae) of central Argentina. Issue 6 (10th September 2015) - Argüello Caro, E.B.; Dumón, A.D.; Mattio, M.F; Alemandri, V.; Truol, G.
Abstract: Planthoppers are important worldwide crop pests as well as vectors of numerous diseases. Different species transmit Mal de Río Cuarto virus, which causes the most economically important corn disease in central Argentina. Epidemiological studies rely on the accurate identification of the species present in the field. Presently, morphological identification of planthoppers requires taxonomic expertise and there are no taxonomic keys for females and nymphs. Nevertheless, no molecular protocols are available for accurate species identification of most frequent delphacid species from central Argentina. In this context, the aim of this study was to evaluate the utility of the cytochrome oxidase I gene (COI) as a DNA barcode and its digestion with restriction enzymes (Restriction Fragment Length Polymorphism, RFLP) for the identification of the most common species of planthoppers in central Argentina. We amplified and sequenced a 843 bp fragment of the COI gene of taxonomically identified specimens and evaluated its use as a DNA barcode. Restriction enzymes were also selected for digesting the COI fragment via RFLP. The high interspecific variability (20.79%; ± 2.32%) and low intraspecific divergence (0.12%; ± 0.17%) observed in the studied species, demonstrate the effectiveness of the COI gene for species identification of major vector delphacids affecting corn crops in Argentina. Moreover, the digestion of this COI gene fragment with Bfa I and Apo I enzymes allows a fast and cost-effective species identification method when numerous specimens need to be processed. Both molecular techniques developed here, allow the accurate identification of planthopper species at regional scale. These new tools would assist traditional identification of these insects, especially for aiding non-experts in morphological taxonomy.